Genotoxicity of Occupational Pesticide Exposures among Agricultural Workers in Arab Countries - Sherif, Moustafa (2023)
Funding Information: This work is supported by the College of Medicine and Health Sciences (CMHS) of the United Arab Emirates University (UAEU) research grant [Grant number: G00003625]. The contribution of MSS and KRM was supported by the United Arab Emirates University PhD grant and the Stipendium Hungaricum Scholarship Programme, respectively. Publisher Copyright: © 2023 by the authors.